N-Acyl Homoserine Lactone-Mediated Quorum Sensing Regulates Species Interactions in Multispecies Biofilm Communities - Subramoni, Sujatha; Muzaki, Muhammad Zulfadhly Bin Mohammad; Booth, Sean C. M.; Kjelleberg, Staffan; Rice, Scott A. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial biofilms are important medically, environmentally and industrially and there is a need to understand the processes that govern functional synergy and dynamics of species within biofilm communities. Here, we have used a model, mixed-species biofilm community comprised of Pseudomonas aeruginosa PAO1, Pseudomonas protegens Pf-5 and Klebsiella pneumoniae KP1. This biofilm community displays higher biomass and increased resilience to antimicrobial stress conditions such as sodium dodecyl sulfate and tobramycin, compared to monospecies biofilm populations. P. aeruginosa is present at low proportions in the community and yet, it plays a critical role in community function, suggesting it acts as a keystone species in this community. To determine the factors that regulate community composition, we focused on P. aeruginosa because of its pronounced impact on community structure and function. Specifically, we evaluated the role of the N-acyl homoserine lactone (AHL) dependent quorum sensing (QS) system of P. aeruginosa PAO1, which regulates group behaviors including biofilm formation and the production of effector molecules. We found that mixed species biofilms containing P. aeruginosa QS mutants had significantly altered proportions of K. pneumoniae and P. protegens populations compared to mixed species biofilms with the wild type P. aeruginosa. Similarly, inactivation of QS effector genes, e.g. rhlA and pvdR, also governed the relative species proportions. While the absence of QS did not alter the proportions of the two species in dual species biofilms of P. aeruginosa and K. pneumoniae, it resulted in significantly lower proportions of P. aeruginosa in dual species biofilms with P. protegens. These observations suggest that QS plays an important role in modulating community biofilm structure and physiology and affects interspecific interactions.